Implementasi Model Problem Based Learning Pada Peserta Didik Tentang Materi Tatacara Bersuci Dari Hadast Besar - Rohim, Saepul; Andiani, Neng Restu (STAI Al-Musaddadiyah Garut, 2025)
In the material of the procrdure for major purification of hadas, students often experience difficulties in implementing it because of the many differences of opinion, especially for students who are new to the material. To overcome this, the problem-based learning (PBL) model is the right choice to improve understanding through a more conceptual approach. The PBL model focuses on the use of problems as a starting point for learning where teachers present peoblems that are relevant to everyday life so as to encourage students to think critically. This study aims to describe the implementation of the PBL model for students on the material of the procedure for purification of major hadas in the fiqh subject phase e at MAN 1 Garut. The study used a qualitative approach with a descriptivr-survey method throug interviews and observations of student behavior. Primary data were obtained from interviews with fiqh feachers and also student interviews. While secondary data sources were obtained from graphie documents such as teaching modules,photod, teaching resources. The results of the study showed that the implementation of the problem-based learning model had a significant influence on students’ undersing of the material of the procedure for major purification of hadas in the fiqh subject phase e at MAN 1 Garut. This study revealed thet students’ contributions wewe greater than the use of other learning models. Keywords: Problem Based Learning